2019
DOI: 10.1186/s12913-019-4569-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a group-based diabetes prevention program within a healthcare delivery system

Abstract: Background Group-based Diabetes Prevention Programs (DPP), aligned with recommendations from the Centers for Disease Control and Prevention, promote clinically significant weight loss and reduce cardio-metabolic risks. Studies have examined implementation of the DPP in community settings, but less is known about its integration in healthcare systems. In 2010, a group-based DPP known as the Group Lifestyle Balance (GLB) was implemented within a large healthcare delivery system in Northern Califo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 38 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…Studies investigating setting or context are useful for the identification of whether an intervention is appropriate or feasible to deliver for a given setting [50][51][52][53]. This allows for understanding uncertainties about the setting and how differences across settings may influence implementation [54][55][56][57]. In some situations, where an existing intervention is adapted to be delivered in a different setting, understanding how the intervention interacts with the new context becomes a key feasibility outcome to evaluate.…”
Section: Considerationsmentioning
confidence: 99%
“…Studies investigating setting or context are useful for the identification of whether an intervention is appropriate or feasible to deliver for a given setting [50][51][52][53]. This allows for understanding uncertainties about the setting and how differences across settings may influence implementation [54][55][56][57]. In some situations, where an existing intervention is adapted to be delivered in a different setting, understanding how the intervention interacts with the new context becomes a key feasibility outcome to evaluate.…”
Section: Considerationsmentioning
confidence: 99%
“…Tables 3, 4 summarise the 90 studies included in the analysis. From these, 36 studies dealt with barriers and enablers to engagement in diabetes prevention progr ammes [21][22][23][24][27][28][29][30][31][32][33][35][36][37][38][39][42][43][44][45][51][52][53][54][56][57][58]64,68,73,88,92,94,97,98,103 (Table 3), 65 studies with programme acceptability 16,[24][25][26][27][28]33,34,37,40,41,43,44,[46]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Conversely, participants who felt confused and uncertain at diagnosis were less likely to participate. 28,36,42 Aujla et al 24 found that people who declined to participate in a diabetes prevention programme were unsure about whether they were at risk of type 2 diabetes. This was supported by Joachim-Célestin et al, 36 whereby health information and referral to a diabetes prevention programme from a health professional prompted enrolment.…”
Section: Healthcare Mechanismsmentioning
confidence: 99%
“…However, participant retention in the program varies by age, race/ethnicity [26], and other behavioral, psychological, and structural factors [27]. Thus, there is a need to consider adaptations and modifications to the program to identify strategies to improve retention and effectiveness [26], as well as alternative modes of implementation/program delivery to overcome barriers [28]. The Vibrant Lives program adapted the DPP program for virtual, light-touch delivery using print materials sent via email, text messages, group challenges, and weight and activity trackers, to improve retention and successful weight loss.…”
Section: Introductionmentioning
confidence: 99%